Un nuevo Hansenochrus Reddell & Cokendolpher, 1995 (Schizomida: Hubbardiidae) de Venezuela noroccidental - Manzanilla, Osvaldo Villarreal; Teruel, Rolando (Papéis Avulsos de Zoologia, 2006)
A new species of Hansenochrus Reddell & Cokendolpher, 1995 is described from a cave in Lara state, in the northwest region of Venezuela, and is its fourth species known from this country. Hansenochrus urbanii sp. nov. represents the first record of this genus from Venezuelan hypogean fauna.